An evaluation of the effectiveness of the roving reference service of the Southville International School college library - Javier, Ramil V.; Dar Juan, Elijah John F. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2016)
Roving reference is a form of reference service where the librarian himself approaches the user for queries. In the Philippines, few studies are done in the effectiveness of roving reference service in academic libraries. An example would be De La Salle University's study of its own Roving information Assistant (RIA) for this study, te chosen institution in Southville International School College Library.
This study is descriptive in nature with 235 out 1,004 undergraduate students as respondents. A survey was done to collect the demographic information of the respondents, confirmation of previous use of the roving reference service, and evaluation of the roving reference service.
The data gathered show that: (a) majority of the users were Information Systems Management, BS Information Technology, and Information Systems Technology majors, were mostly at their 1st, 2nd, and 3rd year level, and they belonged to the 17-19 year old age group; (b) the behaviors displayed by the roving librarian when rendering the service, as observed by users, were positive and inviting in nature; (c) the queries asked by majority of the users were directional and research queries; (d) majority of the users thought the service was very thorough and prompt; (e) majority of the users perceived the service as very effective; (f) uses i.e. [users] pointed at staffing and training, shelving and resources, and user-librarian communication as the points that need improvement. With these findings, it was concluded that the roving reference service of Southville International School College Library was effective.
To broaden the study, a five-year study and comparative study between two libraries that offer roving reference services were recommended. Shifting the focus to the roving libraries. Shifting the focus ti roving librarian himself himself and doing future reference service based on the referencce service based on the aforementioned points of improvement were recommended as well.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Southville International School College Library; Reference services (Libraries) -- Philippines -- Paranaque City -- Evaluation